2010
DOI: 10.1002/elan.201000285
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Studies on the Interaction of Gatifloxacin, Moxifloxacin and Sparfloxacin with DNA and Their Analytical Applications

Abstract: The electrochemical oxidation of the three fluoroquinolone drugs FQs: gatifloxacin GTF, moxifloxacin MXF and sparfloxacin SPF, at the bare and DNA-modified glassy carbon electrodes has been studied by voltammetric techniques. The three FQs showed one irreversible oxidation peak at potential range 0.85-0.91 V vs. Ag-AgCl, in phosphate buffer of pH 7.0. Differential pulse voltammetry (DPV) and UV-absorption spectroscopic techniques were employed to probe the interaction between the FQs and calf thymus double str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The decrease of the I p value of 11% or 21% for CIP in the presence of dsDNA for interaction times of 10 s or 3 h, respectively, when compared to the CIP peak in the absence of the nucleic acid, can be attributed to a decrease of the free drug concentration due to the formation of a slow-diffusion CIP-DNA complex. With the addition of dsDNA, the E p value is positively shied, from 1.076 V (without dsDNA) to 1.097 V (interaction time of 10 s) or 1.108 V (interaction time of 3 h); from this, we infer that the CIP interaction with DNA possibly occurs by intercalation, as previously reported by Fotouhi et al, 34 who used CV and UV-vis spectroscopy, and by Radi et al, 58 who used DPV to analyze the interaction of some FQs with DNA in solution. Radi et al 58 also suggested that the piperazine moiety of FQs plays an important role in binding to dsDNA.…”
Section: Interaction Of Cip With Dnasupporting
confidence: 86%
“…The decrease of the I p value of 11% or 21% for CIP in the presence of dsDNA for interaction times of 10 s or 3 h, respectively, when compared to the CIP peak in the absence of the nucleic acid, can be attributed to a decrease of the free drug concentration due to the formation of a slow-diffusion CIP-DNA complex. With the addition of dsDNA, the E p value is positively shied, from 1.076 V (without dsDNA) to 1.097 V (interaction time of 10 s) or 1.108 V (interaction time of 3 h); from this, we infer that the CIP interaction with DNA possibly occurs by intercalation, as previously reported by Fotouhi et al, 34 who used CV and UV-vis spectroscopy, and by Radi et al, 58 who used DPV to analyze the interaction of some FQs with DNA in solution. Radi et al 58 also suggested that the piperazine moiety of FQs plays an important role in binding to dsDNA.…”
Section: Interaction Of Cip With Dnasupporting
confidence: 86%
“…6 Studies on the interaction between drugs and biological macromolecules can provide a proper understanding of the absorption, transportation, distribution, metabolism, excretion properties and possible mechanism of drugs, thereby are benecial to design, modify and screen drug molecules. 7,8 Previously, the interactions of MOXH with biological macromolecules including calf thymus DNA 2,9 and bovine hemoglobin 3 have been investigated by uorescence spectroscopy. These studies indicated that MOXH could bind to the two biological macromolecules through a static process and affect their structures via different combination types.…”
Section: Introductionmentioning
confidence: 99%
“…No official (pharmacopoeia) method has been found for the assay of GMF and MOX in their pharmaceutical formulations. Several methods have been reported on the determination of fluoroquinolones either in pure forms, in dosage forms, or in biological fluids like chromatography [3][4][5][6], capillary zone electrophoresis [7,8], electrochemistry [9][10][11], atomic absorption spectrometry [12,13], spectrofluorimetry [14][15][16], and spectrophotometric methods for GMF [17][18][19][20][21][22][23][24][25][26][27][28] or MOX [12,[29][30][31][32][33][34][35][36] (Tables 1 and 2). These methods were associated with some major drawbacks such as decreased Scheme 1: The chemical structure of the studied drugs.…”
Section: Introductionmentioning
confidence: 99%